Unsuspected oral pigmentation in patient with systemic disease histories - Sari, Tjut Intan Permata; Agustina, Dewi; Dean, Nathaniel (Faculty of Dentistry, Universitas Gadjah Mada, 2024)
Oral pigmentation refers to a pigmented lesion on the oral mucosa, caused by one or more pigments that accumulate, resulting in tissue color change. Pigment lesions can vary in size, color, and location, and may range from benign to malignant. The role of the dentist is crucial in recognizing and classifying these lesions to facilitate proper treatment. This case report describes oral pigmentary abnormalities suspected to be indicative of an undiagnosed systemic disease. A 52-year-old woman presented with complaints of brittle teeth. Upon examination, changes in her oral mucosa were noted, and she was found to have uncontrolled type 2 diabetes mellitus, as well as a history of hysterectomy due to a tumor. Intraoral and extraoral examination revealed macular pigmentation on the mucosa and skin, particularly on the extremities. After further investigation, we concluded that early detection of polyps is important, as these patients may be susceptible to neoplasia development in areas outside the intestines. Dentists should be vigilant in recognizing a wide range of lesions that can assist in diagnosing conditions beyond oral health, to ensure patients receive appropriate treatment.